2015
DOI: 10.1378/chest.14-2018
|View full text |Cite
|
Sign up to set email alerts
|

Time Trends of Aspirin and Warfarin Use on Stroke and Bleeding Events in Chinese Patients With New-Onset Atrial Fibrillation

Abstract: BACKGROUND:Much of the clinical epidemiology and treatment patterns for patients with atrial fi brillation (AF) are derived from Western populations. Limited data are available on antithrombotic therapy use over time and its impact on the stroke or bleeding events in newly diagnosed Chinese patients with AF. Th e present study investigates time trends in warfarin and aspirin use in China in relation to stroke and bleeding events in a Chinese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 36 publications
0
43
0
1
Order By: Relevance
“…The results of current study show that the OAC treatment in patients with AF may be improving in China, consistent with previous studies. 21 In the quality evaluation of stroke care and treatment (ChinaQUEST) study, 22 which registered patients with recent stroke in 2006, in-hospital OAC use was 11% among patients with nonvalvular AF. In the China National Stroke Registry II conducted from 2012 to 2013, the use of warfarin at discharge among acute ischemic stroke patients with NVAF was only 19.4%.…”
Section: Discussionmentioning
confidence: 99%
“…The results of current study show that the OAC treatment in patients with AF may be improving in China, consistent with previous studies. 21 In the quality evaluation of stroke care and treatment (ChinaQUEST) study, 22 which registered patients with recent stroke in 2006, in-hospital OAC use was 11% among patients with nonvalvular AF. In the China National Stroke Registry II conducted from 2012 to 2013, the use of warfarin at discharge among acute ischemic stroke patients with NVAF was only 19.4%.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the high stroke incidence, only 4.1% of Chinese patients with AF are currently under warfarin therapy . Results from a recently published large‐sample study showed that AF patients taking warfarin did not have lower stroke rate compared to patients taking aspirin, probably due to a poor international standard ratio (INR) control. In non‐valvular atrial fibrillation (NVAF) patients, 90% of cases of atrial thrombi are derived from the left atrial appendage (LAA) .…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, increasing use of warfarin among patients with AF (26.7% in 1992 to 63.1% in 2007) was associated with declining trend in incidence of ischemic stroke but without any significant increase in hemorrhagic stroke rates. 8 However, warfarin is extremely underused 9,10 in Chinese patients with AF, particularly in those with a higher stroke risk. 11,12 Besides physicians' compliance with guideline recommendations for stroke prevention, 13 patients' nonadherence and nonpersistence to warfarin are major barriers to improved anticoagulation treatment in patients with AF.…”
mentioning
confidence: 99%